Analisis Pengaruh Tingkat Inklusi Keuangan Dan Literasi Keuangan Terhadap Minat Menabung Masyarakat Di Bank Syariah Di Indonesia - Hidayanti Shafira; Ersi Sisdianto (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The development of Indonesian sharia financial institutions, especially in the field of sharia banking, has increased every year, where Indonesia is in 5th place in the world. Islamic banks strive to provide convenience for their customers through digital technology-based services, but the market share of Islamic banks is lower than conventional banks. This may be caused by the low level of understanding of sharia finance, sharia financial inclusion. This research aims to analyze whether financial literacy and financial inclusion influence people's interest in saving at Islamic banks. The research results reveal that financial inclusion and financial literacy are recognized as being able to influence people's interest in saving at Islamic banks.